Adesão ao tratamento para lesão crônica no cenário de ensaio clínico - Gleyka Lopes Martins (2020)
Introduction: Adherence to the treatment of chronic wounds proves to be a complex issue for the understanding and management by health professionals especially nurses in the reference services. The success of the proposed therapy, the control and prevention of chronic disease, and the achievement of a cure depends on the patient's adherence to the proposed procedures or therapies. However, adherence can be difficult, for individual and collective reasons. Aspects such as clinical conditions and expectations built with the health team, material and economic, social and cultural conditions, access and use of health services, in addition to psychosocial aspects, such as ways of thinking about the body, illness, treatment, emotions, suffering and expectations about life can be decisive in adherence. In the case of a new treatment, proposed in clinical research, one wonders in what conditions adherence occurs or not, when it comes to people with venous ulcers or diabetic foot ulcers, especially in research which using new drugs. Objective: To understand adherence to the treatment of people with chronic injuries, in the context of a clinical trial. Methodology: This research constituted the qualitative axis of the larger project named “Phase II Clinical Trial of the Skin Healing Action of Proteolytic Fraction of the Latex of Vasconcellea Cundinamarcensis”. For this research, open and in-depth individual interviews were conducted with 15 users of reference services for wound care, public and private, in the city of Belo Horizonte. The data analysis method was the Structural Narration Analysis (AEN). Results and Discussion: The interpretation of the set of qualitative data revealed four central categories 1) What patients experienced in the course of wound treatment, 2) Adherence to wound treatments, 3) Relationship between health professionals versus patients and 4) Motivation to participate in research clinic and other treatments for chronic injuries. There were differences in the distinction between the interviewees emerged both in socioeconomic and psychosocial aspects, reaffirming the multifactorial aspect of this process. The low level of education and income are present and related to the difficulties in understanding the health- disease-care process. There is a denial of the severity of the wound in its initial stage, making it difficult to seek immediate treatment. There is a lack of knowledge concerning the relationship of the wound with other health compromises, with the first care being performed, in general, through home practices. Intense pains that hinder productive activities at work and at home lead to the demand for health services. Respondents define treatment for chronic wounds as "difficult" and "long", plus difficulties due to poor communication, lack of bonds and vanities of professionals, which interfere with treatment adherence. In the clinical research phase, adherence was integral. Everyone said they went to the service because they were well looked after and had hope for the new treatment. The results showed the importance of resilience, which was explained at the end as a theoretical category that encompasses treatment and adherence trajectories. Conclusions: Adherence proves to be a game between objectivity and subjectivity that includes the relationships of professionals with people with chronic wounds, and it is not acquired forever. It should be thought of in the context of resilience, understood as a contextualized, personal and social process, in continuous construction, to be supported, with clarity and care, by health professionals, especially nurses from primary care services and referrals for treatment of chronic wounds.